First identification of blaNDM-5 producing Escherichia coli from neonates and a HIV infected adult in Tanzania. Issue 2 (28th February 2022) - Manyahi, Joel; Moyo, Sabrina J.; Kibwana, Upendo; Goodman, Richard N.; Allman, Ellie; Hubbard, Alasdair T. M.; Blomberg, Bjørn; Langeland, Nina; Roberts, Adam P.
Abstract : Introduction. Carbapenem-resistant members of the family Enterobacteriaceae are emerging as a global public-health threat and cause substantial challenges in clinical practice. Gap Statement. There is a need for increased and continued genomic surveillance of antimicrobial resistance genes globally in order to detect outbreaks and dissemination of clinically important resistance genes and their associated mobile genetic elements in human pathogens. Aim. To describe the resistance mechanisms of carbapenem-resistant Escherichia coli . Methods. Rectal swabs from neonates and newly diagnosed human immunodeficiency virus (HIV) infected adults were collected between April 2017 and May 2018 and screened for faecal carriage of carbapenamases and OXA-48 producing members of the family Enterobacteriaceae. Bacterial isolates were identified using matrix assisted laser desorption ionization time of flight mass spectrometry. Antimicrobial susceptibility testing was performed by E-test. Whole genomes of carbapenem-resistant E. coli were investigated using a hybrid assembly of Illumina and Oxford Nanopore Technologies sequencing reads. Results. Three carbapenem-resistant E. coli were detected, two from neonates and one from an HIV infected adult. All three isolates carried bla NDM-5 . Two E. coli from neonates belonged to ST167 and bla NDM-5 co-existed with bla CTX-M-15 and bla OXA-01, and all were carried on IncFIA type plasmids. The E. coli from the HIV infected adult belonged to ST2083, and carried bla NDM-5 on an IncX3 type plasmid and bla CMY-42 on an IncI type plasmid. All bla NDM-5 carrying plasmids contained conjugation related genes. In addition, E. coli from the HIV infected adult carried three more plasmid types; IncFIA, IncFIB and Col(BS512). One E. coli from a neonate also carried one extra plasmid Col(BS512). All three E. coli harboured resistance genes to fluoroquinolone, aminoglycosides, sulfamethoxazole, trimethoprim, macrolides and tetracycline, carried on the IncFIA type plasmid. Furthermore, E. coli from the neonates carried a chloramphenicol resistance gene ( catB3 ), also on the IncFIA plasmid. All three isolates were susceptible to colistin. Conclusion. This is the first report, to our knowledge, from Tanzania detecting bla NDM-5 producing E. coli. The carbapenemase gene was carried on an IncFIA and IncX3 type plasmids. Our findings highlight the urgent need for a robust antimicrobial resistance (AMR) surveillance system to monitor and rapidly report on the incidence and spread of emerging resistant bacteria in Tanzania.